Direct dehydration of 1, 3-butanediol into butadiene over aluminosilicate catalysts. Issue 15 (25th February 2016) - Jing, F.; Katryniok, B.; Araque, M.; Wojcieszak, R.; Capron, M.; Paul, S.; Daturi, M.; Clacens, J.-M.; De Campo, F.; Liebens, A.; Dumeignil, F.; Pera-Titus, M.
Abstract : The catalytic dehydration of 1, 3 - butanediol into butadiene was investigated over various aluminosilicates with different SiO2 /Al2 O3 ratios and pore architectures. Abstract : The catalytic dehydration of 1, 3-butanediol into butadiene was investigated over various aluminosilicates with different SiO2 /Al2 O3 ratios and pore architectures. A correlation between the catalytic performance and the total number of acid sites and acid strength was established, with a better performance for lower acid site densities as inferred from combined NH3 -TPD, pyridine adsorption and 27 Al-NMR MAS spectroscopy. The presence of native Brønsted acid sites of medium strength was correlated to the formation of butadiene. A maximum butadiene yield of 60% was achieved at 300 °C over H-ZSM-5 with a SiO2 /Al2 O3 ratio of 260 with the simultaneous formation of propylene at a BD/propylene selectivity ratio of 2.5. This catalyst further exhibited a slight deactivation during a 102 h run with a decrease in the conversion from 100% to 80% due to coke deposition as evidenced by XPS and TGA-MS, resulting in a 36% loss of the specific surface area.